Sense of Coherence in Young Patients with Acute Myocardial Infarction and Its Influence on Rehabilitation Knowledge and Self-management Behaviors - Juanli LI; Rong WANG; Ping LIU; Qun LU; Xia XIN (康复学报)
Objective:To investigate the sense of coherence in young patients with acute myocardial infarction, so as to explore its influence on rehabilitation knowledge and self-management behaviors.Methods:A total of 109 qualified young acute myocardial infarction patients were recruited by convenience sampling. Sense of coherence-13,coronary artery disease rehabilitation knowledge questionnaire and coronary artery disease self-management scale were applied to collect data.Results:The score of sense of coherence was (70.16±12.28),which was in the middle level. The score of rehabilitation knowledge was (73.11±11.25).The score of self-management was (83.36±12.41) with the scoring rate of 61.75%.There were significant differences in rehabilitation knowledge and self-management behavior among participants with different SOC levels (P<0.05).Conclusion:The health workers should guide the patients to face the disease with peace of mind, encourage and instruct them to utilize all available resources to face the challenges brought by the disease, improve the sense of coherence, and promote the development of physical and mental health.